The effect of a low-carbohydrate diet on subcutaneous adipose tissue in females with lipedema - Lundanes, Julianne; Gårseth, Mari; Taylor, Shannon; Crescenzi, Rachelle; Pridmore, Michael; Wagnild, Rune; Hyldmo, Åsne Ask; Martins, Catia; Nymo, Siren (Frontiers in Nutrition, 2024)
Introduction: Lipedema is a common, yet underdiagnosed, subcutaneous adipose tissue (SAT) disorder. The main characteristics are SAT expansion in the lower extremities and arms, pain, and tenderness to palpation. It remains unknown if a low-carbohydrate diet (LCD) influences SAT in females with lipedema Objectives: to evaluate the effect of a LCD low-energy diet, compared to a low-fat isoenergetic control diet, on calf subcutaneous adipose tissue area, muscle area, SAT/muscle ratio, calf circumference and body composition in females with lipedema. Subjects/Methods: Adult females with obesity and lipedema were randomized to 1200 kcal/day diets, either LCD or control (75 and 180 g/day of carbohydrates, respectively) for eight weeks. Body composition was measured with bioelectrical impedance analysis, calf SAT area, muscle area, and circumference with magnetic resonance imaging and pain with brief pain inventory, before and after the intervention. Results: Thirteen participants were included (five in the LCD group), with a mean age of 46 ± 12 years and a BMI of 37 ± 6 kg/m 2 . A significant reduction in calf SAT area, calf circumference, and pain was observed in the LCD group only. Both LCD and control groups experienced a significant reduction body weight, fat mass, fat free mass, and muscle area, with no differences between groups. No significant changes over time were found for SAT/muscle ratio. Conclusion: A LCD has the potential to reduce SAT and pain in females with lipedema, despite a reduction in muscle mass in lipedema affected areas in both diet groups. Further studies are needed to confirm these findings and explore potential mechanisms. Clinical trial registry: NCT04632810: Effect of Ketosis on Pain and Quality of Life in Patients With Lipedema (Lipodiet)